On the interpretation of decay-associated fluorescence spectra in proteins - Ladokhin, A.S. (Біополімери і клітина, 2001)
Calculating decay-associated spectra (DAS) is a common mode of analyzing complex fluorescence decay in proteins. Unfortunately, these spectra are attributed almost exclusively to certain species in the population of macromolecules (retainers), often without sufficient evidence. An alternative explanation of decay heterogeneity, based on structural relaxation., was believed to require a negative DAS component. Here we demonstrate that dipolar relaxation of the indole molecule, lacking any rotameric forms, doesn't always result in negative pre-exponential amplitude. We conclude that the shape of DAS alone is not sufficient to differentiate among various causes of heterogeneity of tryptophan fluorescence decay in proteins.